Policy relevant, multidisciplinary, disruptive: What kind of research do economists want? - Peter Andre; Armin Falk (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Based on a global survey of almost 10,000 academic economists, Peter Andre and Armin Falk explore what economists perceive to be worthwhile research in their discipline. Finding many economists think that economic research should become more policy relevant, multidisciplinary, and disruptive, and cover a more diverse range of research topics, they suggest that economics and economists would benefit from a more inclusive discussion of the direction in which the field is travelling.
Keywords: 330